Phonological Errors In The Pronunciation Of Hijaiyyah Letters At Islamic Boarding School/ Kesalahan Fonologis Dalam Pengucapan Huruf Hijaiyyah Di Pondok Pesantren - Musthofa, Tulus; Nasiruddin, Nasiruddin; Rojudin, Didin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The purpose of this study is to analyze the phonological errors of students at the Yogyakarta Fathul Huda Islamic Boarding School in the pronunciation of hijaiyyah letters (halqi letters). This qualitative descriptive research uses data collection techniques such as structured interviews, observations, and documentation. Data analysis used reduction, presentation, and conclusion. The validity of the data through source triangulation techniques. The results of this study indicate that student’s phonological errors are in three aspects, such as the phonetic change in the letters غ-خ-ع-ه. Meanwhile, the phonological errors in the aspect of phoneme reduction are in the pronunciation of the words ضَارٌّ - ضَرٌّ, صَارُوْخٌ - صَرُوْخٌ, عَالَمٌ - عَلَمٌ, غَابَةٌ - غَبَةٌ, حَاسُوْبٌ - حَاسُبٌ, رَحِيْمٌ - رَحِم. And the phonological errors in the element of phonemes addition are in the words يَضْحَكُ – يَضْحَاكُ. Deviations occur due to several factors, including ignorance of the pronunciation of Arabic letters, interference from different dialects of the mother tongue, and the lack of communicative Arabic teaching. To overcome phonological errors of students or speakers, some of the researchers' suggestions include practicing the pronunciation of Arabic letters and letters according to the meaning of the letters and the lengths of vowels and intonation.